2015
DOI: 10.1016/j.jneb.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Self-Weighing Throughout Adolescence and Young Adulthood: Implications for Well-Being

Abstract: Objective This paper describes the prevalence of self-weighing in the transition period from adolescence to young adulthood and examines cross-sectional and longitudinal associations between self-weighing and weight status, psychological, and behavioral outcomes. Design Project EAT (Eating and Activity in Teens and Young Adults), a longitudinal cohort study that assessed variables 3 times over 10 years. Participants 1,868 adolescents and young adults. Main Outcome Measures weight, BMI, weight disparity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Given that self-weighing likely draws attention to the body (Mercurio & Rima, 2011 ) and can highlight discrepancies between current and desired shape or weight (Dionne & Yeudall, 2005 ), self-weighing may result in worse psychological outcomes among those who are sensitive or concerned about their bodies. It is likely that this includes teenagers and young adults (Friend, Bauer, Madden, & Neumark-Sztainer, 2012 ; Pacanowski, Loth, Hannan, Linde, & Neumark-Sztainer, 2015 ; Quick et al, 2012 , 2013 ) and females (Geier & Rozin, 2008 ; Pingitore, Spring, & Garfieldt, 1997 ). It will therefore be important to examine whether and how the nature of the sample influences the association between self-weighing and psychological outcomes.…”
Section: What Factors Influence the Psychological Impact Of Self-weigmentioning
confidence: 99%
“…Given that self-weighing likely draws attention to the body (Mercurio & Rima, 2011 ) and can highlight discrepancies between current and desired shape or weight (Dionne & Yeudall, 2005 ), self-weighing may result in worse psychological outcomes among those who are sensitive or concerned about their bodies. It is likely that this includes teenagers and young adults (Friend, Bauer, Madden, & Neumark-Sztainer, 2012 ; Pacanowski, Loth, Hannan, Linde, & Neumark-Sztainer, 2015 ; Quick et al, 2012 , 2013 ) and females (Geier & Rozin, 2008 ; Pingitore, Spring, & Garfieldt, 1997 ). It will therefore be important to examine whether and how the nature of the sample influences the association between self-weighing and psychological outcomes.…”
Section: What Factors Influence the Psychological Impact Of Self-weigmentioning
confidence: 99%
“…In any case, further observational studies with a larger sample size are necessary to confirm these results. Some studies showed that frequent self-weighing caused an increase in anxiety and depression in younger females and predicted binge eating and unhealthy weight control behavior [13,19]. Because questionnaires regarding unhealthy behaviors such as binge eating and family history of diabetes were not administered to students in the present study, further studies should be conducted to examine ways to refine such types of interventions to improve their efficacy.…”
Section: Discussionmentioning
confidence: 94%
“…However, too much focus on weight can produce important negative psychosocial consequences, particularly among children and adolescents (Birch and Fisher, 1998). A 2015 study of almost 2,000 adolescents and young adults found that a high amount of self-weighing was associated with decreased body satisfaction and self-esteem (Pacanowski et al, 2015). Previous studies by Killen et al (1994) and Rosen et al (1987) found restrained adolescent eaters, such as those trying to lose weight, also exhibited high levels of body dissatisfaction, low self-worth, fear of weight gain, and anxiety.…”
Section: Weight Loss or Healthy Behaviors?mentioning
confidence: 98%